Analysis of fatigue crack propagation under mixed mode II + III in ARMCO iron. (July 2015) - Vojtek, T.; Pokluda, J.; Šandera, P.; Horníková, J.; Hohenwarter, A.; Pippan, R.
Highlights: Mixed-mode II + III fatigue cracks propagation experiments in ARMCO iron were done. Small-scale yielding was verified by both analytical and numerical approaches. The most appropriate expression of mixed-mode crack growth data was found. Mode III component of mixed-mode loading was less efficient than that of mode II. Abstract: Near-threshold propagation of shear cracks under mixed-mode II + III loading was investigated in ARMCO iron. Special specimens for simultaneous growth of cracks in II, III and II + III loading modes were employed in these experiments. All experiments were performed under small-scale yielding as verified by both analytical and numerical approaches. The most appropriate description of mixed-mode crack growth was found in terms of Δ a /Δ N vs. Δ Keq dependences, where Δ K eq = Δ K II 2 + β · Δ K III 2 and β = 1.1. Also another mixed-mode criterion based on averaged using weight coefficients revealed to be useful. These analyses revealed that the mode III component of the mixed-mode loading was slightly less efficient for the mixed-mode crack-growth mechanism than that of the mode II which is in agreement with results reported for some other metallic materials.